2021
DOI: 10.1155/2021/6626484
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Mitochondrial Permeability Transition Pore to Prevent Age‐Associated Cell Damage and Neurodegeneration

Abstract: The aging process is associated with significant alterations in mitochondrial function. These changes in mitochondrial function are thought to involve increased production of reactive oxygen species (ROS), which over time contribute to cell death, senescence, tissue degeneration, and impaired tissue repair. The mitochondrial permeability transition pore (mPTP) is likely to play a critical role in these processes, as increased ROS activates mPTP opening, which further increases ROS production. Injury and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 143 publications
(127 reference statements)
1
27
0
Order By: Relevance
“…Alteration in mPT by chemotherapy might influence cell destiny by altering the physiological activity of mPTPC. As a result, it is suggested that forcing the mitochondrial permeability transition pore (mPTP) to open or close for an extended period of time is toxic to the cell [26,67]. For example, pretreatment of mPT with a pore inhibitor, Cyclosporin A (CsA), or a pore opener sensitizer, PK11195, has been discovered to increase mitochondrial apoptosis triggered by resveratrol, a natural polyphenol [68].…”
Section: Mitochondrial Permeability Transition Pore Complex (Mptpc)mentioning
confidence: 99%
“…Alteration in mPT by chemotherapy might influence cell destiny by altering the physiological activity of mPTPC. As a result, it is suggested that forcing the mitochondrial permeability transition pore (mPTP) to open or close for an extended period of time is toxic to the cell [26,67]. For example, pretreatment of mPT with a pore inhibitor, Cyclosporin A (CsA), or a pore opener sensitizer, PK11195, has been discovered to increase mitochondrial apoptosis triggered by resveratrol, a natural polyphenol [68].…”
Section: Mitochondrial Permeability Transition Pore Complex (Mptpc)mentioning
confidence: 99%
“…mtCa 2+ overload is one of the major causes of mPTP opening ( Kwong, 2017 ). The opening of the mPTP can cause mitochondrial depolarization and ROS production ( Kent et al, 2021 ). In our observations, sorafenib and regorafenib increased mtCa 2+ overload, which was evidenced by the calcium indicator mito-pericam.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial ROS production and induction of apoptosis is closely related to many degenerative diseases, including neurodegeneration [ 55 , 56 , 57 ]. In the current study, we showed mitochondrial ERβ-dependent resistance in the induction of apoptosis upon treatment of the cells with either the apoptotic stimulus staurosporine or the oxidative stress stimulus H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%